TMR, MRE, and X-ray photoelectron spectroscopy of Fe-SiO₂ granular films - Kravets, V.G.; Poperenko, L.V.; Vinnichenko, K.L. (Functional Materials, 2005)
Feₓ(Si0₂)₁₋ₓ magnetic granular films below the percolation threshold (х < 0.45) have been studied using tunneling magnetoresistance (TMR), magnetorefractive effect (MRE), and X-ray photoelectron spectroscopy. Maximum magnetoresistance ratio of 3.7 % at room temperature was observed for films of Fe₀.₃₅(Si0₂)₀.₆₅ composition. Both the experimental and theoretical analysis reveal a correlation between TMR and MRE, thus demonstrating the usage possibility of the MRE as a contactless method to measure the TMR. The chemical surface structure was analyzed by X-ray photoelectron spectroscopy (XPS) and compared to that of the corresponding Si0₂ and Fe surfaces. The XPS spectra of Feₓ(Si0₂)₁₋ₓ granular films display two main peaks at 707 and 720 eV, which arise from Fe 2р₃/₂ and Fe 2р₁/₂, respectively, and a small peak appears around 710.5 eV due to Fe₂0₃. Магнитные гранулированные пленки Feₓ(Si0₂)₁₋ₓ с содержанием металла ниже порога перколяции изучены с помощью туннельного магнитосопротивления, магниторефрактивного эффекта и рентгеновской фотоэлектронной спектроскопии. Максимальное значение магнитосопротивления 3,7 % при комнатной температуре было обнаружено для пленок Fe₀.₃₅(Si0₂)₀.₆₅. Экспериментальные результаты и теоретический анализ показывают корреляцию между туннельным магнитосопротивлением (ТМС) и магниторефрактивным эффектом (МРЭ), что позволяет использовать МРЭ в качестве бесконтактного метода измерения ТМС. Химический состав поверхности пленок проанализирован с помощью рентгеновской фотоэлектронной спектроскопии (РФС) и проведено его сравнение с поверхностями Si0₂ и Fe. РФС спектры гранулированных пленок Feₓ(Si0₂)₁₋ₓ характеризуются двумя полосами, локализованными при энергиях 707 и 720 эВ, которые связаны с Fe 2р₃/₂ и Fe 2р₁/₂ энергетическими уровнями. Также наблюдался незначительный пик при 710,5 эВ благодаря вкладу Fe₂0₃. Магнiтнi гранулярнi плiвки Feₓ(Si0₂)₁₋ₓ iз змiстом металу, нижчим за перколяцiйний порiг, дослiджувались за допомогою тунельного магнiтоопору, магнiторефрактивного ефекту та рентгенiвської фотоелектронної спектроскопiї. Максимальне значення магнiтоопору 3,7 % при кiмнатнiй температурi було знайдено для плiвок Fe₀.₃₅(Si0₂)₀.₆₅. Експериментальнi результати та теоретичний аналiз показують кореляцiю мiж тунельним магнiтоопором (ТМО) та магнiторефрактивним ефектом (МРЕ). Це дозволяє використовувати МРЕ для безконтактного вимiрювання ТМО. Хiмiчний склад поверхнi плiвок Feₓ(Si0₂)₁₋ₓ аналiзувався за допомогою рентгенiвської фотоелектронної спектроскопiї (РФС) та порiвнювався з даними для поверхонь Si0₂ i Fe. РФС-спектри гранульованих плiвок Feₓ(Si0₂)₁₋ₓ характеризуються двома смугами при енергiях 707 та 720 еВ, якi вiдповiдають енергетичним рiвням Fe 2р₃/₂ та Fe 2р₁/₂. Також спостерiгався незначний максимум при 710,5 еВ завдяки внеску Fe₂0₃.